PRODUKSI ETANOL MENGGUNAKAN Saccharomyces cerevisiae - Ari Sudono, ; Surya Rosa Putra, (Matematika dan Sains, 2010)
The aims of this research were to study the effect of S. cereviseae amobilized at agarose on subtrat consumtion pattern and ethanol production during fermentation process using optimum of agarose concentration, pH, and glucose concentration. The concentration of ethanol and glucose were determined by gas chromatography and Somogyi-Nelson method, respectively. The results of this research showed that the optimum of agarose concentration, pH, glucose concentration, and fermentation time were 3%; 4,5; 10 %; and 31 hours, respectively. During 31 hours, amobilized cell produced ethanol 5,20% (percent yield of 80,3%) and the remaining glucose of 0,03%, while the free cell produced ethanol 3,61% (percent yield of 56%) with the remaining glucose of 1,2%. Thus the amobilized cell could produce ethanol 30% larger than the free cell. The amobilized cell used continuously in four times fermentation only caused degradation of ethanol concentration of 5,1%. The amobilized cell saved for 10 days without medium and nutrition still could produced ethanol of 4,87% and only 7,6 % lower than amobilized cell used directly.